MAKNA DAN IKLAN MEDIA CETAK: KAJIAN HIPERSEMIOKA - MULYAWAN, I WAYAN (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
ABSTRACT Besides language exploitation phenomenon, in an advertisement, the presence of non-verbal elements also indicate the same phenomenon, whereas between non-verbal sign and the products or services that is being advertise sometimes have no relation in meaning at all and even reflect unrealistic meaning. In order to uncover the insight of this non-realistic meaning, it is required a special approach of hyperrealistic meaning theory that is Hypersemiotics.